Pinyin Pronunciation Development in Chinese using the Chinese Pinyin Game application for Students majoring in Chinese Teaching Program,RajabhatMahasarakhamUniversity,Thailand - Phupunna, Suphasa; Hongsamsibkao, Nareerat; Sripol, Chinnawat; Khumdumrongkiet, Chanakan (Journal of Education Rajabhat Maha Sarakham University, 2021)
This research aimed to develop Pinyin pronunciation achievement in Chinese with Chinese Pinyin Game application. The sample of this research was 56 students in the first year of Chinese teaching program, Faculty of Education, Rajabhat Mahasarakham University of 2019. Research instruments was featured with Chinese Pinyin Game Application. The data was analyzed by using mean, standard deviation and t-test. The results showed that after learning with the Chinese Pinyin Game application, the score was 51.62 when individually considered; the sound group generated from front tip of tongue sound z c s had average score of 14.57 (S.D. = 0.68), the sound group generated from front tonguesound j q x had average score of 14.10 (S.D. = 1.29), the sound group generated from back tip of tongue sound zhchsh r had average of 11.26 (S.D. = 2.98) and vowel sound ü ieüe üanün had average score of 11.91 (S.D. = 2.84). When comparison the pre-test with post-test scores, it was found that.